2020
DOI: 10.1088/1748-9326/ab7b9b
|View full text |Cite
|
Sign up to set email alerts
|

Warming-induced unprecedented high-elevation forest growth over the monsoonal Tibetan Plateau

Abstract: Growth of high-elevation forests is generally temperature-limited and thus sensitive to warming. The Tibetan Plateau has experienced fast warming rates associated with decreased summer monsoon rainfall over the last century. However, whether such warming and monsoon-induced drought could offset a potential warming-driven enhancement of forest growth has not been examined. Here, we have compiled high-elevation forest growth data at 40 sites over the monsoonal Tibetan Plateau (MTP), and combined them in a high-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Numerous investigations have set out to describe the changes in radial growth of tree species by elevation gradient by means of dendrochronological analyses (Ponocná et al 2016;Lanza et al 2018;Panthi et al 2018, Shi et al 2020. The present study found a relationship between radial growth and elevation in 18 (32.1%) of the dendrochronological studies analyzed.…”
Section: Radial Growth-elevationsupporting
confidence: 54%
See 3 more Smart Citations
“…Numerous investigations have set out to describe the changes in radial growth of tree species by elevation gradient by means of dendrochronological analyses (Ponocná et al 2016;Lanza et al 2018;Panthi et al 2018, Shi et al 2020. The present study found a relationship between radial growth and elevation in 18 (32.1%) of the dendrochronological studies analyzed.…”
Section: Radial Growth-elevationsupporting
confidence: 54%
“…The wide variation in the results obtained in the relationship between radial growth and elevation in tree species, as well as the low percentage of studies that found some type of significative association between the two (ࣘ10.7%), is probably a consequence of heterogeneity in environmental conditions and of phenomena related to elevation, e.g. changes in surface soil, atmospheric pressure, temperature, rainfall, or solar radiation (Körner 2007;Shi et al 2020). It may also be that an elevation effect is masked by other variables that were not measured (Vitali et al 2017).…”
Section: Radial Growth-elevationmentioning
confidence: 99%
See 2 more Smart Citations
“…Our diagnostic model showed that the enhanced photosynthesis is largely stimulated by temperature, radiation absorption and FPAR. Even though associated with declination in summer monsoon rainfall, increased temperature has significantly positive correlation with tree growth ( R 2 = 0.53, p < 0.001) and was found to promote the growth of alpine forests on TP (Shi et al., 2020). Here we show that up to 5% increase in GPP can be attributed to temperature despite the associated declination in soil moisture (Figure 8).…”
Section: Discussionmentioning
confidence: 99%